Closing the Gap: the Five Essential Attributes of the Modern Information Professional. (10th December 2014) - Lord, Simon
Abstract This paper is based on a research study commissioned by the Financial Times and the Special Libraries Association (SLA) to explore the evolving value of information management to organisations around the world. Drawing on responses from both full-time information professionals and corporate executives, the research highlights the challenges facing both audiences and reveals a fundamental shift in the model of information management. The paper aims to provide an actionable framework for the continuing success of the information function in any organisation, describing the five essential attributes for modern information professionals. The research was presented by Simon Lord at the BIALL Annual Conference, 2014 and is published in full at: www.ft.com/sla